RadCases head and neck imaging - Shah, Gaurang; Wesolowski, Jeffrey (Jeffrey Robert); Choi, Jeanie (Jeanie M.), 1973-; Friedman, Elliot R. (RadCases., 2016)
"This volume on Head and Neck Imaging will complete the corpus of content for the RadCases series. As with all RadCases volumes, Head and Neck Imaging contains 100 cases in the print book and an additional 150 cases online. The content covers the imaging of the various structures of the head and neck, including the temporal bone, the skull base, all ear and orbit structures, all nanasal structures and paranasal sinuses, the neck and its structures and glands, the larynx, etc. Following the proven RadCases format, each case begins with the clinical presentation on the first page, and the second page provides image findings, differential diagnoses, definitive diagnoses, essential facts, Pearls and Pitfalls, all with high-quality images. RadCases simulates what the resident finds on rounds, rotations, and exams"--Provided by publisher